Recent developments of almond culture in the southeast Anatolia region of Turkey - Naska N.; Ozcan Z.; Ak B.E. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Almond growing in South East Anatolia developed quite rapidly over the past five years due to the availability of high quality irrigation water, fertile soils, productive, late flowering and early bearing cultivars, no damage from late spring frosts and high profits. So, almond is going to be an alternative nut to pistachio, which is the main nut grown in the area. Commercial almond orchard establishment started in 1999 by NUR-MET. The trees started bearing fruit at the third leaf. At the fourth leaf, the yield was satisfactory. Over the past 5 years, the total acreage achieved about 200 ha. In all the new orchards the trees were budded on bitter almonds and all of them were irrigated using either the drip, basin or flood method, pruned and fertilized every year. In this paper the results of phenological and pomological investigations of different cultivars and the recent developments of almond growing in the GAP region are presented.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)